Energy Performance Development of Non-regulated Retrofit Mass Housing Estates in Northern Cyprus. (28th July 2017) - Ozarisoy, Bertug; Altan, Hasim
Abstract: This research project was undertaken in the Turkish Republic of Northern Cyprus (T.R.N.C). The objective of the research is to investigate the occupants' behaviour and role in the refurbishment activity; to explore how and why occupants decide to change building components and to understand why and how occupants consider using energy-efficient materials. The study is conducted through semi-structured interviews to identify occupants' behaviour as it is associated with refurbishment activity. This research paper presents the results of semi-structured interviews with 70 homeowners in a selected group of 16 housing estates in four different regions of the T.R.N.C. The expected solutions should be effective, environmentally acceptable and feasible given the type of housing projects under review, with due regard for their location, the climatic conditions within which they were undertaken, the socio-economic standing of the house owners and their attitudes, local resources and legislative constraints. Furthermore, the study goes on to insist on the practical and long-term economic benefits of refurbishment under the proper conditions and why this should be fully understood by the householders.